Association between residential greenness and severe psychological distress and the moderating role of ‘stay-at-home’ status: a population-based cross-sectional study during the COVID-19 pandemic in Japan - Takeo Fujiwara; Yuna Koyama; Hisaaki Nishimura; Nobutoshi Nawa; Yui Yamaoka; Jin Kuramochi (BMJ Public Health, 2023)
Objective There is a need for public health strategies to address the negative psychological consequences of the COVID-19 pandemic, and the role of residential green exposure has gained prominence, particularly in the context of the ‘new normal’ and the prevailing ‘stay-at-home’ policies. This study aimed to evaluate the association between residential greenness and severe psychological distress during the COVID-19 pandemic in Japan. We also investigated the association stratified by ‘stay-at-home’ status, a proxy for exposure to residential greenness.Methods and analysis We used data from a population-based cohort study conducted in Utsunomiya City, Japan. Residential greenness was measured by the normalised difference vegetation index (NDVI) averaged over circular buffers around residence. Severe psychological distress was defined as a Kessler Psychological Distress Scale (K6) score ≥13. ‘Stay-at-home’ status was categorised as either ‘not stay-at-home’ (individuals working outside the home or self-employed) or ‘stay-at-home’ (working from home or not working), based on the working status. Logistic regression analysis was performed to examine the association between residential greenness and severe psychological distress.Results A total of 615 participants were analysed. Among the ‘stay-at-home’ group, an IQR increase in NDVI was inversely associated with severe psychological distress (100 m buffer: OR=0.27, 95% CI 0.10 to 0.77; 250 m buffer: OR=0.26, 95% CI 0.10 to 0.69; 500 m buffer: OR=0.33, 95% CI 0.11 to 0.95). However, no significant association was observed for the ‘not stay-at-home’ group.Conclusion Residential greenness was a protective factor for severe psychological distress among the ‘stay-at-home’ group, who were assumed to have spent more time in their residence.